(untitled) (AYUSHDHARA, 2019)
Darshana Shastra is the outcome of comprehensive perception of nature, which explains and narrate the state of human existence. Darshanas and Ayurveda both are having same source that is Veda. Objectives of Ayurveda is to accomplish the physical, mental, social and spiritual well being by adopting the preventive and promotive approach as well as treating the diseases with various remissive approaches. Darshanas are the path to get free from miseries and to attain ultimate happiness i.e., Moksha which is the goal of life. Yoga Darshana is one of the oldest practices of Hindu tradition which is considered as path for Moksha. Tattvas of Yoga Darshana are merely influenced on Ayurveda. So, it is a need of hour to study the historical background of Yoga Darshana and some Sanskrit scholars explains that, Praneta of Charaka Samhita, Mahabhashya and Yoga Shastra was the same person. This paper throws a light on critical analysis of Charaka and Patanjali.